Interaction between graphene-coated nanowires revisited with transformation optics - Jiang, Jing (2020)
The interaction between graphene-coated nanostructures provides interesting optical properties not found in isolated graphene plasmonic structures. However, full-analytical solutions, which can provide deep physical insights underlying the hybrid graphene plasmonic systems, are difficult to achieve. In this Letter, we deploy the theory of transformation optics to study the plasmonic interactions between two dielectric-core-graphene-shell nanowires. The scattering and absorption spectra as well as the field distributions are derived analytically. We find that the interaction between two graphene-coated nanowires results in polarization-independent multi-frequency Fano dips, which show a broadband red shift of bonding modes and a blue shift of anti-bonding modes when the nanowires approach each other. The analytical tool presented here offers a rigorous study of graphene plasmonic compound and can be extended to treat more complicated cases.